An Analysis of The Causes Of Low Community Participation In Waste Management In Cimohong Village, Bulakamba District, Brebes Regency - Urfah Markhumah; Siti Khumayah (ann4publisher@gmail.com, 2026)
Background. Waste management remains a serious environmental issue in rural areas, including in Cimohong Village, Bulakamba Subdistrict, Brebes Regency. Low levels of public awareness and participation in waste management have led to waste accumulation and environmental pollution, negatively affecting the community's health and social conditions. Aims. This study aims to examine the level of public awareness and participation in waste management, identify the factors contributing to low community involvement, and analyze efforts to improve community-based waste management. This study employs Soetomo’s theory of community participation, which encompasses the dimensions of planning, implementation, utilization of results, and program evaluation. Methods. The research method used is a descriptive qualitative approach through interviews, observations, and documentation. The results indicate that public awareness remains low, as evidenced by the habit of indiscriminately discarding and burning waste, as well as by the lack of separation between organic and inorganic waste. Result. The contributing factors include sociocultural, economic, and educational factors, weak institutional capacity, limited waste collection facilities, and insufficient environmental education. Conclusion. Efforts undertaken include increasing public awareness, providing waste management facilities, and strengthening the role of village governments as well as community participation.